Security Concerns in Cloud Computing for Knowledge Management Systems - Gunadham, Thanyatida; Kuacharoen, Pramote (Journal of Applied Statistics and Information Technology, 2016)
This study discusses major security issues and concerns related to cloud computing environment in regard to knowledge management system processes such as knowledge creation, refining, storing, sharing, and utilization. This study uses the exploratory approach to address major security concerns and whether they need consideration for each knowledge management process. The result of this study reveals main cloud computing security concerns such as data security and confidentiality issues, access controls, data loss or leakage prevention, cyber-attacks, availability and reliability issues, and browser security and analyzes these security concerns from knowledge management systems’ point of view. Also, solutions and recommendations for security concerns are discussed to provide guidance for the organization initiating cloud-based knowledge management systems.